2017
DOI: 10.1002/2211-5463.12216
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen inhibits starvation‐induced apoptosis in osteocytes by a redox‐independent process involving association of JNK and glutathione S‐transferase P1‐1

Abstract: Estrogen deficiency causes bone loss as a result of microdamage, oxidative stress, and osteocyte apoptosis. A relationship between oxidative stress‐induced apoptosis, c‐Jun N‐terminal kinase (JNK) activation, and expression of factors involved in bone remodeling has been demonstrated in osteocytes. However, the molecular regulation of these events in osteocytes treated with 17β‐estradiol (17β‐E2) remains unexplored. The MLO‐Y4 murine osteocyte‐like cell line was used as a model to study starvation‐induced apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 56 publications
(168 reference statements)
3
35
0
Order By: Relevance
“…*P ≤ 0.001 compared to BJand BE-treated cells without EX527 or with Scr siRNA; ○ P ≤ 0.01 compared to the respective untreated starved cells with EX527 or with SIRT1 siRNA; Δ P ≤ 0.001 compared to untreated starved cells. similar to what occurs in vivo in the bone environment after microdamage and oestrogen deficiency [12,14,18,26,47]. Previously, it has been demonstrated that oxidative stress-induced apoptosis by starvation in MLO-Y4 cells is involved in the up-regulation of osteoclastogenic factors [18].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…*P ≤ 0.001 compared to BJand BE-treated cells without EX527 or with Scr siRNA; ○ P ≤ 0.01 compared to the respective untreated starved cells with EX527 or with SIRT1 siRNA; Δ P ≤ 0.001 compared to untreated starved cells. similar to what occurs in vivo in the bone environment after microdamage and oestrogen deficiency [12,14,18,26,47]. Previously, it has been demonstrated that oxidative stress-induced apoptosis by starvation in MLO-Y4 cells is involved in the up-regulation of osteoclastogenic factors [18].…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, polyphenol-derived phenolic acid present in serum from BB diet-fed rats is bioactive, stimulating osteoblast differentiation and bone mineralization through Wnt signalling [2,23]. Previous data demonstrated that in MLO-Y4 cells, starvation-induced apoptosis is closely related to increased mitochondrial ROS production, which, through JNK activity, induces caspase-3 activation [18,47]. Furthermore, this study demonstrates that the antiapoptotic ability (apoptosis reduction of about 70-80%) of BJ and BE is higher than their antioxidant capacity (ROS reduction of about 50%).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed an observed increase in the aortic JNK activity in the OVX and VD-sufficient group compared to the SHAM. This could be explained by withdrawal of estrogen's JNKsuppressor effect [46] and menopause-associated oxidative stress, dyslipidaemia, and inflammatory cytokines that are known stressors activating JNK [42].…”
Section: Discussionmentioning
confidence: 99%
“…GSTP1, a dimeric protein, binds to JNK and suppresses downstream JNK g signaling (36). To the best of our knowledge, the JNK signaling pathway is involved in the processes of cell death and mediates stress-induced apoptosis via mitochondrial pathways with the release of cytochrome c-activating caspases (CASP3, -6, and -7) (36,37). Therefore, the present study detected the expression of P38, ERK, USP33, TCF4 and GSTP1.…”
Section: Discussionmentioning
confidence: 81%
“…The phosphorylation of TCF4 at the serine/threonine proceeds via ERK and p-38 dependent pathways, and TcF4 knockdown has been shown to induce growth arrest and apoptosis in human colorectal cancer (34,35). GSTP1, a dimeric protein, binds to JNK and suppresses downstream JNK g signaling (36). To the best of our knowledge, the JNK signaling pathway is involved in the processes of cell death and mediates stress-induced apoptosis via mitochondrial pathways with the release of cytochrome c-activating caspases (CASP3, -6, and -7) (36,37).…”
Section: Discussionmentioning
confidence: 99%